2010
DOI: 10.1021/ac101798t
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectrochemical detection of pentachlorophenol with a Multiple Hybrid CdSexTe1−x/TiO2 Nanotube Structure-Based Label-Free Immunosensor

Abstract: Driven by the urgent demand of detecting trace amounts of pentachlorophenol (PCP) in contaminative water, a label-free immunosensor with ultra sensitivity and high selectivity was constructed based on a hybrid CdSe(x)Te(1-x) (0 ≤ x ≤ 1) nanocrystal (NCs)-modified TiO(2) nanotube (NT) arrays for the first time. The CdSe(x)Te(1-x) NCs were photoelectrodeposited on inner and outer space of the TiO(2) NTs, leading to high photoelectrical conversion efficiency in the visible region. PCP antibodies are covalently co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
111
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(113 citation statements)
references
References 35 publications
0
111
0
2
Order By: Relevance
“…3,4 Moreover, the European Union and the US EPA have strictly limited the maximum admissible concentration (0.5 ppb and 1 ppb, respectively) of PCP in drinking water. 5,6 Thus, extensive efforts have been made towards the trace and ultratrace detection of PCP in the last decade. Various methods, including capillary electrophoresis, 7 gas chromatography (GC), 8 gas chromatography-mass spectrometry (GC-MS), 9 highperformance liquid chromatography (HPLC) 10 and uores-cence detection (FL) 11 have been explored for the measurement of PCP.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Moreover, the European Union and the US EPA have strictly limited the maximum admissible concentration (0.5 ppb and 1 ppb, respectively) of PCP in drinking water. 5,6 Thus, extensive efforts have been made towards the trace and ultratrace detection of PCP in the last decade. Various methods, including capillary electrophoresis, 7 gas chromatography (GC), 8 gas chromatography-mass spectrometry (GC-MS), 9 highperformance liquid chromatography (HPLC) 10 and uores-cence detection (FL) 11 have been explored for the measurement of PCP.…”
Section: Introductionmentioning
confidence: 99%
“…Immunoassays have attracted interest with the expectation of obtaining prompt, accurate, and sensitive immunological response for food safety, environmental monitoring, and medical and clinical diagnosis (Liu et al, 2008;Tang et al, 2008). Some PEC analysis on the determination of anticholera toxin antibody (Haddour et al, 2006;Haddour et al, 2004), α-fetoprotein (Wang et al, 2009a), mouse immunoglobulin G (Wang et al, 2009b) and pentachlorophenol (Kang et al, 2010) have been reported in the past decade. In these investigations, the label-free method, which is based on the direct antibody-antigen affinity without markers, has been chosen for the purpose of saving time and cost (Haddour et al, 2006(Haddour et al, , 2004Kang et al, 2010;Wang et al, 2009aWang et al, , 2009b.…”
Section: Introductionmentioning
confidence: 99%
“…Some PEC analysis on the determination of anticholera toxin antibody (Haddour et al, 2006;Haddour et al, 2004), α-fetoprotein (Wang et al, 2009a), mouse immunoglobulin G (Wang et al, 2009b) and pentachlorophenol (Kang et al, 2010) have been reported in the past decade. In these investigations, the label-free method, which is based on the direct antibody-antigen affinity without markers, has been chosen for the purpose of saving time and cost (Haddour et al, 2006(Haddour et al, , 2004Kang et al, 2010;Wang et al, 2009aWang et al, , 2009b. Despite the good simplicity of the PEC label-free immunosensor, the sensitivity still needs to be improved due to the low capacity of analyte loading and inability for amplification .…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] From these studies, molecular-semiconductor hetero-interfaces (such as protein-TiO 2 , 14,15 DNA-quantum dots, 16,17 organic molecule-silicon, 18 redox molecule-nanowires 19 and photoactive molecule-nanowires 20 ) have been applied to adjust photoelectrochemical (PEC) activities by enhancing the efficiency of PEC conversion. [21][22][23][24] In PEC-based bioanalysis (for example, DNA analysis, [25][26][27] immunoassays [28][29][30][31] and enzymatic sensing 32 ), PECenzymatic sensing has been the focus of considerable research because of the facile and inexpensive fabrication of appropriate interfaces and, more importantly, their high sensitivities and specificities. 33,34 In addition, third-generation PEC enzyme biosensors based on direct electrochemistry have been shown to be capable of direct electron transfer between their active sites and electrodes.…”
Section: Introductionmentioning
confidence: 99%